Research, publication, and desirable impact. How not to die trying? - Cabezas, César (2018)
It is considered that the main objective of health research is to contribute to improving the well-being and living conditions of people, but what we see in reality is that the performance of researchers is usually measured by the scientific quality of their research, more than for its impact on health. This is markedly insufficient, which is why good weather is trying to devise a way to measure the social impact of applied health research (1). Ideally all investigations should be of high quality and have a considerable social impact on the improvement of health; however, factually scientific quality and social impact do not always walk together. The scientific publication is in the middle of that process that must go from research to the utility of the evidence.